EFECTO DE LA SUSTANCIA P SOBRE LA PRESIÓN ARTERIAL PULMONAR EN POLLOS EXPUESTOS A LA ALTURA - Bernilla De la C., Sebastiana (2003)
Hypoxia at high altitude produces pulmonary arterial hypertension as a result of pulmonary arteriolar vasoconstriction, but the mechanism of action is still unknown. Under these conditions, vasoactive substances like Substance P (SP), are synthesized in the vascular endothelium. To study the effect of SP on the mean pulmonary arterial pressure (PAPm), 30 male chickens for meat production, born and reared at sea level were used. The birds were exposed at 35 days of age to 3,320 m of altitude for 3 days, and then the PAPm was determined by catheterising the pulmonary artery, both before (Pre–SP) and after (Post–SP) injection of SP in doses of 0.30 mcg (0.3ml)/kg of body weight. The mean value of PAPm for Pre–SP was 37.92 ± 4.10 mm Hg, while for Post–SP at the times of 01, 05, 10, 15, 30, 45, 60, 75 and 90 seconds were 36.08 ± 3.70, 31.11 ± 7.51, 28.00 ± 10.22, 26.43 ± 11.02, 24.43 ± 11.02, 23.17 ± 11.54, 24.08 ± 10.98, 27.27 ± 10.97, and 30.67 ± 9.40 mm Hg, respectively. SP significatively diminished the PAPm (p < 0.001) from the 1st second and reached his lowest value at 45 seconds. The quick decrease of PAPm suggests a possible influence of SP at vascular endothelial level through its vasodilator effect, decreasing the press effect that could be related to the hyperpolarization of the membrane as well as to an increase of nitric oxide activity.